Atm Is Dispensable for p53 Apoptosis and Tumor Suppression Triggered by Cell Cycle Dysfunction - Liao, Mai-Jing (American Society for Microbiology, 1999)
Both p53 and ATM are checkpoint regulators with roles in genetic stabilization and cancer susceptibility. ATM appears to function in the same DNA damage checkpoint pathway as p53. However, ATM’s role in p53-dependent apoptosis and tumor suppression in response to cell cycle dysregulation is unknown. In this study, we tested the role of murine ataxia telangiectasia protein (Atm) in a transgenic mouse brain tumor model in which p53-mediated apoptosis results in tumor suppression. These p53-mediated activities are induced by tissue-specific inactivation of pRb family proteins by a truncated simian virus 40 large T antigen in brain epithelium. We show that p53-dependent apoptosis, transactivation, and tumor suppression are unaffected by Atm deficiency, suggesting that signaling in the DNA damage pathway is distinct from that in the oncogene-induced pathway. In addition, we show that Atm deficiency has no overall effect on tumor growth and progression in this model.